Prevalence of intestinal parasites and risk factors in schoolchlidren in Chicamocha Kenedy I schoolin the municipality of Tuta, Boyaca - Colombia - Suescún Carrero, Sandra Helena (Universidad y Salud, 2013)
Objective: To determine the prevalence of intestinal parasites and identify the risk factors in school children from school Chicamocha Kennedy I section in the municipality of Tuta Boyacá. Methods: A cross-sectional study with correlative phase was made with 50 schoolchildren from ages 7 to 12. The presence of intestinal parasites was tested from a direct stool examination, and risk factors were evaluated through a structured survey which included general, housing, socio-economic, biological, behavioral and environmental aspects. The processing and statistical analysis was carried out with the program SPSS 19 version. Results: The prevalence of parasites was 96% CI 95% (90%-101%). The most common parasites were Blastocystis spp.(88%); G. intestinalis (34%); Entamoeba coli (56%); and the complex Entamoeba histolytica/dispar (24%). The polyparasitism was very important (84%), finding up to a maximum of 4 species per host. 54% are girls of rural dominance. Statistically significant association between parasitism and the excreta disposal was found (X 2 = 11, 492; p = 0, 003), and the lack of washing hands before eating (X 2 = 4, 0044; p = 0, 044). Conclusions: This study shows a high prevalence of intestinal parasites, especially of Blastocystis spp.